2022
DOI: 10.3390/foods11071064
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and Bioaccessibility of Bioactive Compounds in Gastrointestinal Digestion of Tomato Bagasse Extracts

Abstract: A nutrient-rich diet is a key to improving the chemical signals, such as antioxidants, which modulate pathogens’ resistance in the gut and prevent diseases. A current industrial problem is the generation of undervalued by-products, such as tomato bagasse, which are rich in bioactive compounds and of commercial interest (carotenoids and phenolic compounds). This work analyzed the effect of gastrointestinal digestion on the bioactivity and bioaccessibility of carotenoids and phenolic compounds from tomato bagass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…[8] Even if BCs can reach the intestinal tract, their bioaccessibility is greatly reduced due to their hydrophobicity. [9] Some BCs used as drugs are often limited by multiple intestinal epithelial absorption barriers. It was reported that transcellular oral BCs must across the epithelium through three sequential cellular barriers including apical endocytosis, intracellular trafficking, and basolateral exocytosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Even if BCs can reach the intestinal tract, their bioaccessibility is greatly reduced due to their hydrophobicity. [9] Some BCs used as drugs are often limited by multiple intestinal epithelial absorption barriers. It was reported that transcellular oral BCs must across the epithelium through three sequential cellular barriers including apical endocytosis, intracellular trafficking, and basolateral exocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Even if BCs can reach the intestinal tract, their bioaccessibility is greatly reduced due to their hydrophobicity. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that consumption of sea cucumber could attenuate the ROS formation in the human body [17]. The availability of bioactive peptides in sea cucumbers could be increased through enzymatic hydrolysis [13,19] or released naturally during gastrointestinal digestion [20].…”
Section: Introductionmentioning
confidence: 99%
“…Not all of them, when consumed, can enter into the bloodstream and induce beneficial health effects. 14,15 For this reason, it is very important to know how these compounds are released from the matrix and are bioaccessible in the different phases of the digestive tract. 16 The in vitro gastrointestinal digestion system is a tool for investigating the behavior of bioactive compounds present in food products during human digestion.…”
Section: Introductionmentioning
confidence: 99%
“…However, in order for the food to exert a beneficial effect on health, the bioactive compounds present must be able to withstand food processing and be bioavailable. Not all of them, when consumed, can enter into the bloodstream and induce beneficial health effects 14,15 . For this reason, it is very important to know how these compounds are released from the matrix and are bioaccessible in the different phases of the digestive tract 16 .…”
Section: Introductionmentioning
confidence: 99%